2013
DOI: 10.1103/physrevb.88.060101
|View full text |Cite
|
Sign up to set email alerts
|

Photon energy dependence of graphitization threshold for diamond irradiated with an intense XUV FEL pulse

Abstract: We studied experimentally and theoretically the structural transition of diamond under an irradiation with an intense femtosecond extreme ultraviolet laser (XUV) pulse of 24-275 eV photon energy provided by free-electron lasers. Experimental results obtained show that the irradiated diamond undergoes a solid-to-solid phase transition to graphite, and not to an amorphous state. Our theoretical findings suggest that the nature of this transition is nonthermal, stimulated by a change of the interatomic potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 19 publications
(16 reference statements)
6
36
1
Order By: Relevance
“…The VUV-XUV range was studied in our previous work. 43 It was found that in this regime the critical fluence for the material damage was E th = 0.7 eV/atom in terms of the absorbed dose, in good agreement with the experimental findings. 43 For photon energies above the K edge, our simulations indicate that, although the transient kinetics is different as it includes K-shell hole creation and relaxation (for details see Secs.…”
Section: A Damage Threshold In Diamondsupporting
confidence: 77%
See 4 more Smart Citations
“…The VUV-XUV range was studied in our previous work. 43 It was found that in this regime the critical fluence for the material damage was E th = 0.7 eV/atom in terms of the absorbed dose, in good agreement with the experimental findings. 43 For photon energies above the K edge, our simulations indicate that, although the transient kinetics is different as it includes K-shell hole creation and relaxation (for details see Secs.…”
Section: A Damage Threshold In Diamondsupporting
confidence: 77%
“…As already shown in Ref. 43, the band gap starts to collapse when the fraction of the conduction-band electrons reaches a value of ∼1.5% of the initial number of valence electrons, which corresponds to an absorbed dose of ∼0.7 eV/atom. The induced collapse of the band gap and the increase of the free-electron density trigger a fast relocation of atoms to their new equilibrium positions in the graphite state.…”
Section: Effect Of Incoming Photon Energy On Transient Kineticsmentioning
confidence: 83%
See 3 more Smart Citations